Pediatric emergencies : a practical, clinical guide - Rose, Emily, MD (New York, NY : Oxford University Press, 2020)
'Pediatric Emergencies' comprehensively covers the practical management of pediatric emergencies based on organ systems, with a strong emphasis on clinical relevance. Each chapter explores the background, classic clinical presentation, atypical clinical presentation, differential diagnosis, diagnostic confirmation, treatment, clinical algorithm, disposition, complications, and pitfalls of each topic.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 15, 2020).
Keywords: Pediatric emergencies